EXPLORING THE INTERCONNECTEDNESS OF INTERNAL COLONIZATION AND MIMICRY IN GEORGE ORWELL’S ANIMAL FARM: A POST-COLONIAL ANALYSIS - Ruly Indra Darmawan (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
In Animal Farm, George Orwell introduces mimicry and internal colonisation. Mimicry, a basic notion in human imitation, is used to study Napoleon and his porcine companions. Homi K. Bhabha's ambivalence and “same but not quite” theory examines mimicry. The pigs' behaviour is explained by these post-colonial theories. This study also shows how internal colonisation underlies narrative mimicry. This study claims that the story's copying indicates colonization's lasting effects and is a strategy for internal colonisation. Old Major's clear speech inspires Animal Farm residents to imitate humans, making them feel inadequate. This study reveals how internal or external colonisation divides colonised people. In this approach, people may adopt the conquering entity's cultural norms and values as superior. Another group may be indigenous. Internal colonisation by another party or associated group could result through imitation rivalry. This level requires imitation to demonstrate power. Animal Farm exemplifies colonised people imitating colonisers. This detailed analysis of Animal Farm by George Orwell shows how imitation and internal colonisation are interconnected.